Citizenship education: A media literacy course taught in Japanese university. (April 2022) - Nguyen, Van Thanh
This case study documents the effort to prototype a media literacy curriculum based on Herman and Chomsky (2010)'s Propaganda Model as well as the target students' environment and need analysis. The course is implemented under a Content and Language Integrated Learning program for 30 first-year undergraduate students in Sophia University, Japan. The objective is to develop students' awareness of issues facing society they live in, along with the capacity to think critically about media information, deliberate in public discourse via expression of individual opinions, and exchange with others. Evaluation study is conducted upon completion of the course to examine whether, or to what extent, that objective is realized, using qualitative method. Results show positive impacts on students' learning, providing valuable inputs for further iterations of curriculum design in citizenship and media literacy education.